Maximizing Employee Performance: An Analysis of Organizational and Individual Factors - Novitasari, Dewiana; Asbari, Masduki; PURWANTO, AGUS (IJOSMAS, 2020)
This study aimed to measure the effect of perceived organizational support (organizational factor) on the performance of private company employees in West Java which is mediated by employee engagement (individual factor). The data collection was done by simple random sampling via electronic to the employees as population. The returned and valid questionnaire results were 221 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that perceived organizational support has a positive and significant effect on the employee's performance, both directly and indirectly through mediating employee engagement. This new research proposed a model for building performance among the private company employees in West Java through enhancing perceived organizational support with employee engagements as a mediator